(untitled) (Journal of Medicine, 2024)
Introduction: Stroke is a major health hazard in both developed and developing countries. Dyslipidaemia is one of the important risk factors for stroke. The purpose of the present study was to identify clinical presentations of both ischaemic and haemorrhagic stroke, and to find out correlation between stroke and lipid profile. Methods: The observational study was conducted in the Department of Medicine at Sher-e-Bangla Medical College Hospital, Barishal from April to September 2013 for a period of 6 months. All the stroke patients over 20 years of age of both sexes were selected as study population. After admission at the hospital, history was taken from the patients or the attendants. The clinical presentation was recorded in a pre designed data collection sheet. Fasting lipid profile was measured in every stroke patient. Results: Total 100 stroke patients were enrolled for this study, of them 36 were haemorrhagic and 64 were ischaemic stroke patients. The mean ± SD of age were 63.945 ± 8.84 and 62.26 ± 14.40 in haemorrhagic and ischaemic stroke patients respectively (p>0.05). Among both haemorrhagic and ischaemic stroke patients maximum 61.1% and 60.9% used to have sedentary work. Impaired level of consciousness was more common among the haemorrhagic stroke patients (91.7%) than ischaemic stroke patients (57.8%) group and the association is statistically significant (p=0.001). Limb weakness was the commonest presentation in both haemorrhagic (91.7%) and ischaemic (87.5%) stroke patients. The mean ± SD of total cholesterol was 173.47 ± 61.96 and 178.22 ± 54.79 in haemorrhagic stroke and ischaemic stroke patients respectively (p<0.05). Conclusion: Older age, male sex, sedentary work and dyslipidaemia were susceptible to be affected in stroke. Among lipoproteins, elevated total cholesterols, triglycerides and LDL showed strong correlation with both ischaemic and haemorrhagic strokes. J MEDICINE 2024; 25: 24-28